(untitled) (Cambridge, 2000)
After an introductory review of market trends, the book discusses recent research on the interactions between stress, food and mood, looking a particular at the role of carbohydrates, then it reviews current evidence for the impat of a number of nutrients and herbal ingredients on mood and cognitive performance; including herbs such as St John's wort and kava kava. It also discusses the range of medicinal plants which have been associated with improvements in mental and physical perfoemance.
Thực phẩm chức năng,Thực phẩm chức năng
Keywords: Food technology